Swimming Exercise Therapy Method Case Study of Pinched Nerve Sufferenrs - Nur Aina; Eka Purnama Indah; Aryadi Rachman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Pinched nerves are a disease experienced by many people in Indonesia. Most suffer during the productive age period of 30-60 years. Sufferers of a pinched nerve will experience that if a pinched nerve occurs in the lower back, there will be sharp pain in one part of the waist, groin, legs, feet, hips or buttocks, and even numbness in the back of the calf or sole of the foot. The aim of this study was to determine the effect of regular swimming on reducing pain in people with pinched nerves. This research design uses direct demonstration and the sampling technique uses incidental sampling. The results of this study were that there was an effect of regular swimming on reducing pinched nerve pain from an initial VAS score of 8 (controlled severe pain) to 2 (mild pain). The conclusions in this study show a significant increase in pain reduction, which is expected in cases of pinched nerves or HNP and good treatment with regular swimming.